" Obbedite alle autorità costituite ": Sacralità del potere e possibilità della disobbedienza nella riflessione politica medievale - Simonetta, Stefano (Revue des sciences philosophiques et théologiques, 2023)
Chapter 13 of The Epistle to the Romans lays the foundations on which the whole conception of power in medieval political thought is based. The aim of this paper is to reconstruct the long-term process through which the Latin West gradually came to admit and theorise the possibility of disobeying temporal authorities, albeit within a theoretical framework of power (namely the Pauline-Augustinian one), which would seem to leave no room for dissent, conferring on every potestas a divine origin and providential nature. The author traces the main stages of this process : from the idea that in order to obtain unconditional obedience from one's subjects, one must show oneself a " rex christianissimus " (protecting both the persons and property of Christ's ministers), to the difficult legitimisation of tyrannicide in John of Salisbury ; from the pages of Thomas Aquinas on the deposition of a ruler who does not care about the communis utilitas, to the explicit recognition of the power to dismiss secular lords by some political theorists of the 14th and 15th centuries.